2021
DOI: 10.2399/ana.21.885318
|View full text |Cite
|
Sign up to set email alerts
|

Can Whitnall’s tubercle be localized using palpable landmarks around the orbit?

Abstract: Objectives: Whitnall’s tubercle (WT) is located deep in the lateral canthus and on the lateral orbital wall and has crucial structures attach to it. We aimed to define the location of WT using the palpable bone landmarks which can be used as reliable landmarks in eyelid and orbital surgery to prevent the damage of stuctures associated with WT. Methods: Forty-four adult skulls (22 right, 22 left) were included to the study. The skulls were divided into two groups according to the apparancy of the WT. The distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
(22 reference statements)
1
2
1
Order By: Relevance
“…Besides the fact that the WT is a crucial point for detecting the attachment of lateral retinaculum, the FZs is proved to be a reliable marker for identifying it. 23,24 In the absence of WT, to find the location of attachment of lateral retinaculum, in addition to FZs, we support the study of Korkmaz et al 13 declaring that MT, APoZA, and the closest point of the lateral margin of the orbital rim can also be used.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Besides the fact that the WT is a crucial point for detecting the attachment of lateral retinaculum, the FZs is proved to be a reliable marker for identifying it. 23,24 In the absence of WT, to find the location of attachment of lateral retinaculum, in addition to FZs, we support the study of Korkmaz et al 13 declaring that MT, APoZA, and the closest point of the lateral margin of the orbital rim can also be used.…”
Section: Discussionsupporting
confidence: 83%
“…At the left zygomatic bones, according to the MT, WT were most frequently located at 9 o'clock in our study (70%), whereas Korkmaz and colleagues reported that 59% were located at 8 o'clock. According to the APoZA, WT of the right zygomatic bones were most frequently located at 1 o'clock in our study (92%), whereas Korkmaz et al 13 reported that 91% were located at 2 o'clock. At the left zygomatic bones, according to the APoZA, WT were most frequently located at 11 o'clock in our study (77%), whereas Korkmaz and colleagues reported that 100% were located at 11 o'clock.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations